2002
DOI: 10.3928/0147-7447-20020601-18
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Relaxin and Knee Joint Laxity in Female Athletes

Abstract: Gravidity studies have intimated a relationship between serum relaxin levels and joint laxity. To assess its applicability to eumenorrheic athletes, weekly serum relaxin and knee arthrometry measurements were obtained in 57 collegiate women and 5 men for 4 consecutive weeks. The former included athletes, ACL-injured athletes, and nonathletes, while the latter formed an a priori hormonal control. Analysis of variance revealed a significant change in weekly serum relaxin levels in females but not in anterior tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Of the initial library screened, 82 articles were included for scoping review (1,4,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). There was overlap between analysis categories for numerous papers; most prevalent with the subjects are of cellular/molecular and systemic-musculoskeletal effects.…”
Section: Data Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the initial library screened, 82 articles were included for scoping review (1,4,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). There was overlap between analysis categories for numerous papers; most prevalent with the subjects are of cellular/molecular and systemic-musculoskeletal effects.…”
Section: Data Analysis Resultsmentioning
confidence: 99%
“…Multiple factors contribute to the female predominance of ACL injuries, including neuromuscular discrepancies and fluctuating levels of reproductive hormones (7). Hormonal research has recently identified a promising target: relaxin (1,(7)(8)(9)(10). This has not been investigated in relation to young athletic hip conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxin can lead to ligament laxity by its anti-fibrotic effects. Elevated RLN2 serum levels can increase pelvic width and height in pregnant cattle (48) , as well as tendon 29 and joint laxity (49)(50)(51) in humans. The relaxin receptor RXFP1 has been found in human female anterior cruciate ligaments (52) .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, on the other hand, relaxin has been implemented in joint disorders such as in tearing of the oblique volar ligament in the trapeziometacarpal joint [ 38 ] and in anterior cruciate ligament tears in female athletes [ 43 , 55 ]. In our cohort of dogs with CCLD, there were also more female (13) than male dogs (five), which is in accordance with known epidemiologic data in dogs: there is a 2-fold increased risk for developing cruciate ligament rupture in female dogs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%